2015
DOI: 10.1093/humrep/dev128
|View full text |Cite
|
Sign up to set email alerts
|

Live birth after autograft of ovarian tissue cryopreserved during childhood: Figure 1

Abstract: Ovarian insufficiency is a major long-term adverse event, following the administration of a myeloablative conditioning regimen, and occurring in >80% of children and adolescents receiving such treatment for malignant or non-malignant disease. Cryopreservation of ovarian tissue is currently offered to preserve the fertility of these young patients. At least 35 live births have been reported after transplantation of cryopreserved ovarian tissue in adult patients, but the procedure remains unproven for ovarian ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
211
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(221 citation statements)
references
References 14 publications
2
211
0
8
Order By: Relevance
“…Two recent reports suggest that this technique may be of benefit in preserving fertility in young girls [26, 27], and this will be a subject for future research.…”
Section: Premature Ovarian Insufficiency In Ccsmentioning
confidence: 99%
“…Two recent reports suggest that this technique may be of benefit in preserving fertility in young girls [26, 27], and this will be a subject for future research.…”
Section: Premature Ovarian Insufficiency In Ccsmentioning
confidence: 99%
“…However, it may keep its potential for restoring an endocrine function following thawing and transplantation (58). In addition, the competence of ovarian tissue in term of gametic production has recently been demonstrated with the first live birth obtained after transplantation of ovarian tissue recovered from a premenarchal girl (59). Yet, data on efficiency of this approach in girls or women with TS are lacking.…”
Section: Ovarian Tissue Cryopreservationmentioning
confidence: 99%
“…16,46,47 Based on combined data from three centers in Europe, ovarian tissue transplant resulted in pregnancies in 11/60 cases. 16,48 However, in general, it is difficult to gauge the overall success rate of ovarian tissue transplantation because failures are rarely reported in the literature, and thus the denominator of attempted cases is largely unknown. Several in vivo transplants have occurred in pediatric patients, allowing entry into puberty.…”
Section: Figmentioning
confidence: 99%
“…Of note, it was recently reported that a live birth was obtained following transplantation of ovarian tissue that had been harvested from an individual and cryopreserved prior to menarche. 48 Based on the data gathered through the OC-NPC, it is clear that the use of OTC has increased substantially over the past FIG. 4.…”
Section: Figmentioning
confidence: 99%